Structural Transformations and Adsorption of Fuel-Related Gases of a Structurally Responsive Nickel Phosphonate Metal--Organic Framework, Ni-STA-12. - Miller, Stuart A.; Pearce, Gordon M.; Wright, Paul A.; Bonino, Francesca; Chavan, Sachin; Bordiga, Silvia; Margiolaki, Irene; Guillou, Nathalie; Férey, Gérard; Bourrelly, Sandrine; Llewellyn, Philip L. (Journal of the American Chemical Society, 2008)
The structure of the nickel N,N′-piperazinebismethylenephosphonate, Ni-STA-12 (St. Andrews porous material-12), has been determined in the hydrated (NiL∙8HO, L = OPCHNCHNCHPO), partially dehydrated (NiL∙2HO), and fully dehydrated (NiL) forms from high-resolution synchrotron X-ray powder diffraction. The framework structures of NiL∙8HO and NiL∙2HO are almost identical (R¯3, a = 27.8342(1) Å, c= 6.2421(2) Å; R¯3, a = 27.9144(1) Å, c= 6.1655(2) Å) with additional physisorbed water of the as-prepared Ni-STA-12 present in an ordered hydrogen-bonded network in the channels. Ab initio structure solution of the fully dehydrated solid indicates it has changed symmetry to triclinic (PL a = 6.03475(5) Å, b = 14.9157(2) Å, c 16.1572(2) Å, α = 1 12.5721(7)°, β = 95.7025(11)°, γ = 96.4950(11)°) as a result of a topotactic structural rearrangement. The fully dehydrated solid possesses permanent porosity with elliptical channels 8 Å × 9 Å in free diameter. The structural change results from the loss of water coordinated to the nickel cations, so that the nickel coordination changes from edge-sharing octahedral NiON to edge- and corner-sharing five-fold NiON. During this change, two out of three phosphonate groups rotate to become fully coordinated to nickel cations, leaving the remainder of the phosphonate groups coordinated to nickel cations by two oxygen atoms and with a P=O bond projecting into the channels. This transformation, which is completely reversible, causes substantial changes in both vibrational and electronic properties as shown by IR, Raman and UV-visible spectroscopies. Complementary adsorption, calorimetric, and infrared studies of the probe adsorbates H, CO, and CO reveal the presence of several distinct adsorption sites in the solid, which are attributed to their interactions with nickel cations which are weak Lewis acid sites, as well as with P=O groups that project into the pores. At 304 K, the adsorption isotherms and enthalpies of adsorption on dehydrated Ni-STA-12 have been measured for CO and CH: Ni-STA-12 gives adsorption uptakes of CO of 2.5 mmol g at 1 bar, an uptake ca. 10 times that of CH.